Mechanical characterization and properties of continuous wave laser irradiated Ge2Sb2Te5 stripes. (April 2021) - D'Arrigo, G.; Scuderi, M.; Mio, A.; Favarò, G.; Conte, M.; Sciuto, A.; Buscema, M.; Li-Destri, G.; Carria, E.; Mello, D.; Calabretta, M.; Sitta, A.; et al.
Abstract: Crystalline micrometer size stripes in 2.2 μ m thick Ge2 Sb2 Te5 phase-change material films were produced by irradiation with a Continuous Wave Laser of 405 nm wavelength. The shape and the dimensions of the crystallized regions were investigated by Transmission Electron Microscopy and then compared with simulations based on temperature-crystal growth velocity literature data. The temperature-time profile was determined taking into account the laser power, the optical and thermal properties of both the amorphous and crystalline phase. The mechanical properties of the amorphous and of the crystallized regions were characterized by an ultra nano-indentation technique. This procedure allows a direct and local measurement of hardness and Young's modulus in the amorphous and in the contiguous crystalline regions on the micrometer scale. The following values for Young's modulus and for hardness were obtained: 33±4 GPa and 2.00±0.3 GPa for the amorphous phase, and 51±8 GPa and 2.90±0.45 GPa for the crystalline phase. The stresses induced by the density increase in the crystallized region cause, on the irradiated surface, a series of fracture whose characteristic behavior depends on the laser power and on the spacing between two contiguous scans. These results are of relevance for the mechanical failure mechanisms in potential phase-change devices. Graphical abstract: Unlabelled Image Highlights: Crystallized micrometric lines are defined by Continuous Wave Laser irradiation into amorphous Ge2 Sb2 Te5 Phase Change Material. Transmission electron micrographs show shrunk crystalline symmetric domes for isolated scans and asymmetric for multi-scans due to the heating overlap. Shrinkage produce fractures and delamination indicating that the maximum tensile stress is reached firstly in amorphous regions. Nanoindentation allows a direct and local measurement of hardness and Young's modulus of the contiguous amorphous and crystalline regions.